The Role of Tumor-Associated Macrophage Density to Tumor Size and Lymph Node Metastases of Invasive Ductal Carcinoma Patients at Dr. Soedarso General Hospital Pontianak - Nugraha, Muhammad Fikri; Pratiwi, Sari Eka; Ilmiawan, Muhammad In'am; Trianto, Heru Fajar; Fitrianingrum, Iit; Hartono, Hengky (http://dharmais.co.id/, 2024)
Background: Invasive ductal carcinoma is the most common form of breast cancer worldwide and has a high mortality rate. The main component of the innate immune system in the tumor environment is the tumor-associated macrophage (TAM). Certain types of TAM are known to affect tumor size and lymph node metastasis which makes the cancer prognosis worse. Currently, TAM identification is generally identified using immunohistochemical staining techniques that require high costs and special expertise. An easy and inexpensive TAM identification technique is needed in determining breast cancer prognostic factors. This study focused on TAM density and its role in tumor size and lymph node metastases of invasive ductal carcinoma patients.Methods: This research is an observational analytic study using a cross-sectional approach. This study was conducted by observing the Hematoxylin-Eosin (HE) preparation of invasive ductal carcinoma patients. This study used 55 medical record data and histopathology laboratory reports of invasive ductal carcinoma patients at Dr. Soedarso General Hospital Pathological Anatomy Laboratory. TAM density cut-off is measured by calculating the median data of TAM density. Research analysis was performed using Spearman’s rho correlation test in SPSS version 24.Results: The cut-off value for determining TAM density obtained from observations based on the average value was 29. The highest number of tumor size groups was T4, and the highest number of lymph node metastases was N2. TAM density was significantly not correlated to tumor size (p = 0.285, p 0.05) and lymph node metastases (p = 0.479, p 0.05) Conclusions: This study found no significant correlation between TAM density, assessed through a cost-effective method using HE staining, and tumor size or lymph node metastasis in invasive ductal carcinoma patients.